COMPARATIVE EFFECTS OF ANIMATED AND NON-ANIMATED COMPUTER ASSISTED INSTRUCTIONS ON STUDENTS' ACHIEVEMENT IN BIOLOGY IN AWKA SOUTH LGA OF ANAMBRA STATE (UNIZIK Journal of STM Education, 2025)
This study investigated the comparative effects of animated and non-animated computerassisted instructions (CAI) on students' achievement in Biology in Awka South Local Government Area of Anambra State, Nigeria. The research aimed to determine whether the use of animated CAI, which incorporates dynamic visual and interactive elements, yields better academic outcomes compared to non-animated CAI, which relies on static visuals and text. A quasi-experimental design was employed, involving a sample of senior secondary school students divided into two groups: one exposed to animated CAI and the other to non-animated CAI. Pre-test and post-test assessments were conducted to measure students' achievement levels before and after the intervention. Our pretest-posttest control group design was nonrandomized. The study was guided by two research questions two hypotheses. The population of the students consist 2,036 senior secondary school one (1) Biology students (1,006 males and 1,030 females) in the 17 public secondary schools in Awka South Local Government Area. Participants in the study included 120 SS I Biology students from two public secondary schools in Awka South Local Government area. The instrument used for data collection was Biology Achievement Test (BAT). The tool was verified. Kuder-Richardson Formula 20 (KR-20) was used to determine the instrument's reliability, and the results showed a reliability coefficient of 0.84. The research questions were answered using mean and standard deviation, and the research hypotheses were tested using Analysis of Covariance (ANCOVA). The findings revealed that students taught with animated CAI achieved significantly higher scores in Biology than those taught with non-animated CAI. The study concludes that animated CAI is more effective in enhancing students' understanding and retention of Biological concepts, likely due to its engaging and interactive nature. Recommendations include the integration of animated CAI into the Biology curriculum and the provision of training for teachers to effectively utilize such technologies in the classroom. This research contributes to the growing body of knowledge on the impact of instructional technologies on science education in Nigeria.
Keywords: Achievement, Animation, Biology, Computer Assisted Instruction, Non Animation